Coordination Engineering of Ultra‐Uniform Ruthenium Nanoclusters as Efficient Multifunctional Catalysts for Zinc–Air Batteries. Issue 10 (11th August 2022) - Guo, Yingying; Wu, Donghai; Li, Minhan; Wang, Kaixi; Zhang, Shouren; He, Guangli; Yin, Hengbo; Huang, Chenyu; Yang, Baocheng; Zhang, Jianan
Abstract : The lack of highly efficient, inexpensive catalysts severely hinders the large‐scale application of electrochemical energy conversion technologies (e.g., electrochemical hydrogen evolution reaction (HER) for hydrogen production, metal–air batteries (Cathode: oxygen reduction reaction (ORR))). As a new class of nanomaterials with a high ratio of surface atoms and tunable composition and electronic structure, metal nanocluster (NCs) are promising candidates as catalysts. Herein, a novel catalyst using S, N‐doped carbon matrix (NSCSs) is synthesized to efficiently stabilize high density and ultra‐uniform ruthenium (Ru) nanoclusters (Ru@NSCSs) by small‐molecule self‐assembly pyrolysis approach. The obtained Ru@NSCSs catalyst exhibits outstanding HER activity in all pH conditions (especially with a low overpotential of 5 mV at a current density of 10 mA cm −2 in 1 m KOH) and excellent ORR performance (half‐wave potential ( E 1/2 ) of 0.854 V in 0.1 m KOH). Based on the experimental investigations and theoretical calculations, it is discovered that the S‐atom can modulate the electronic structure and optimization of redox states on the surficial sites of Ru NCs during the ORR process. This work provides a feasible strategy for understanding and regulating the metal–support interface of ultra‐uniform nanoclusters catalysts. Abstract : A novel catalyst using S, N‐doped carbon matrix is synthesized to efficiently stabilize high density and ultra‐uniform ruthenium (Ru) nanoclusters (Ru@NSCSs) by small‐molecule self‐assembly pyrolysis approach. The centerpiece is the coordination of N, S atoms that optimizes the interface structure of *RuS, N sites, which is beneficial to the development of multifunctional and highly active catalysts.